Exploring the Multifaceted Nature of Occupational Stress Among Nurses: A Systematic Review - Sundram, Bala Murali; Vallasamy, Suriya Kumareswaran; Muhadi, Umairah (UI Scholars Hub, 2024)
This systematic review examined occupational stress among nurses, its multifaceted nature, and its significant impact on healthcare delivery and nurse well-being globally. This study identified various stressors, including intrinsic job factors, organizational structure, role expectations, interpersonal relationships, and career development. Using the Cooper and Marshall stress model, a thorough literature search was conducted across databases like ISI Web of Knowledge, PubMed, Scopus, Ovid Medline, and Google Scholar, focusing on publications from 2010 to 2023. This rigorous approach included diverse research methodologies, emphasizing studies measuring outcomes related to occupational stress and mental health among nurses. A total of 10 studies met the inclusion criteria, highlighting stressors such as workload, job demand, job insecurity, and less reward, categorized into five primary sources. The review revealed that occupational stress in nursing is a global issue, leading to adverse outcomes like burnout, decreased job satisfaction, and increased turnover. The discussion emphasized the need for a holistic approach to stress management, advocating for supportive work environments, adequate staffing, and professional development opportunities. In conclusion, strategic interventions are crucial for improving mental health, job satisfaction, and healthcare quality, necessitating collaborative efforts from healthcare leaders, policymakers, and practitioners.